Políticas educacionais e currículo: concepções e vivências de professoras inseridas no sistema municipal de educação de Cabedelo/PB - Porto , Sandra Valéria de Almeida (2015)
This study aimed to analyze the teachers’ discourse (conceptions and experiences) on the movement of curriculum planning and how these teachers articulated their views and experiences to the discussions of Educational Policy for Elementary Education. The research was conducted with ten teachers acting in elementary school (1st to 5th grade) in a municipal public school in Cabedelo, Paraiba. The study adopted a qualitative research methodology, using ethnography as guideline and articulating it to the methodology of the Critical Discourse Analysis, as argues Norman Fairclough. To collect the discourses were used as tools: observations (in classrooms, in pedagogical meetings and collective spaces), questionnaire, semi-structured interviews and audio recordings. Even recognizing that the subject was not new, interest in this research arose because it’s recurrence among researchers in the field, being problematized in most cases in relation to the poor quality of public education, despite recent technical and scientific innovations occurred and occurring within the curriculum policies. The results point to an ambivalence as to what is the curriculum planning within the school and to the fact that not only are the teachers solely responsible for the changes that need to take place in the educational system, although they are the most charged for these transformations. This study wants to contribute to the ongoing debate that is taking shape in the Brazilian educational policy configured by the possibility to construct a more egalitarian public school and accessible to all.